Cultural journeys into the Arab world : a literary anthology - Cohen-Mor, Dalya, 1948- (State University of New York Press, 2018)
Cultural Journeys into the Arab World provides a fascinating window into Arab culture and society through the voices of its own writers and poets. Organized thematically, the anthology features more than fifty texts, including poems, essays, stories, novels, memoirs, eyewitness accounts, and life histories, by leading male and female authors from across the Arabic-speaking world. Each theme is explored in several genres, both fiction and nonfiction, and framed by a wealth of contextual information that places the literary texts within the historical, political, cultural, and social background of the region. Spanning a century of Arab creative writing--from the "dean of Arabic letters" Taha Hussein to the Nobel laureate Naguib Mahfouz and the celebrated poet Adonis--the anthology offers unforgettable journeys into the rich and dynamic realm of Arab culture. Representing a wide range of settings, viewpoints, and socioeconomic backgrounds, the characters speak of their conditions, aspirations, struggles, and achievements living in complex societies marked by tensions arising from the persistence of older traditions and the impact of modernity. Their myriad voices paint a vivid and intimate portrait of contemporary Arab life in the Middle East, revealing the common humanity of a region of vital significance in world affairs.